Germanium-doped and germanium/nitrogen-codoped carbon nanotubes with highly enhanced activity for oxygen reduction in alkaline medium. Issue 76 (1st August 2016) - Wang, Fang; Liu, Ziwu; Li, Meng; Wang, Quan-De
Abstract : Novel Ge-doped and Ge/N-codoped carbon nanotubes were prepared by chemical vapor deposition. Results indicate that the as-prepared Ge-containing carbon nanotubes exhibited superior activities and durability for O2 reduction in alkaline medium. Abstract : To develop effective cathode electrocatalysts for the oxygen reduction reaction (ORR) in fuel cells, germanium (Ge)-doped and Ge/N-co-doped carbon nanotubes (CNTs) were synthesized by chemical vapor deposition in this work. Electrochemical tests demonstrated that the as-prepared Ge-doped and GeN-codoped CNTs exhibited obviously enhanced ORR activity in alkaline medium, showing that the doping of Ge into the carbon matrix could also improve the ORR activities of the CNTs and N-CNTs as in the cases of other reported heteroatoms and would be of great importance for designing more effective ORR electrocatalysts in future alkaline fuel cells.